2016
DOI: 10.3758/s13421-016-0602-2
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting potential markers of storage and rehearsal: Implications for studies of verbal short-term memory and neuropsychological cases

Abstract: Neuropsychological studies of verbal short-term memory have often focused on two signature effects -phonological similarity and word length -the absence of which has been taken to indicate problems in phonological storage and rehearsal respectively. In the present study we present a possible alternative reading of such data, namely that the absence of these effects can follow as a consequence of an individual's poor level of recall. Data from a large normative sample of 251 adult participants were re-analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
(144 reference statements)
0
9
0
Order By: Relevance
“…Also, it is possible that older adults struggled to implement the strategy because it was visually based—some previous research suggests that visual WM declines more in healthy ageing than verbal WM (e.g., Johnson et al, 2010 ). Similarly, more older than younger adults in our uninstructed control group reported using a sub-vocal Rehearsal strategy, that is, silent repetition of verbal labels for material to be recalled (see Logie et al, 1996 ; Wang et al, 2016 ). Specifically, 4 younger and 25 older adults used this strategy in the three N-back tasks combined (see Figure 4 ), supporting previous suggestions that older adults may rely more on verbal rehearsal even in visual WM tasks ( Forsberg et al, 2019 ).…”
Section: Discussionmentioning
confidence: 92%
“…Also, it is possible that older adults struggled to implement the strategy because it was visually based—some previous research suggests that visual WM declines more in healthy ageing than verbal WM (e.g., Johnson et al, 2010 ). Similarly, more older than younger adults in our uninstructed control group reported using a sub-vocal Rehearsal strategy, that is, silent repetition of verbal labels for material to be recalled (see Logie et al, 1996 ; Wang et al, 2016 ). Specifically, 4 younger and 25 older adults used this strategy in the three N-back tasks combined (see Figure 4 ), supporting previous suggestions that older adults may rely more on verbal rehearsal even in visual WM tasks ( Forsberg et al, 2019 ).…”
Section: Discussionmentioning
confidence: 92%
“…For example, Saito, Logie, Morita, & Law (2008) showed that participants used both visual and verbal codes to retain visually presented letter and word sequences (see also Logie, Saito, Morita, Varma, & Norris, 2016;. When a visual stimulus is translated into a verbal code it can be maintained in memory via sub-vocal rehearsal, i.e., silent repetition of verbal labels for material to be recalled (see Logie, Della Sala, Laiacona, Chalmers, & Wynn, 1996;Wang, Logie, & Jarrold, 2016). Sub-vocal rehearsal is an essential feature of the 'phonological loop' (Baddeley, 1986(Baddeley, , 1992Baddeley, Lewis, & Vallar, 1984 ), part of the multi-component model of working memory (Baddeley & Hitch, 1974;Baddeley, 1986;Baddeley & Logie, 1999).…”
Section: Take Down Policymentioning
confidence: 99%
“…Developmental improvements in WM may, for example, be driven by increases in storage capacity (Cowan, Ricker, Clark, Hinrichs, & Glass, 2014) and / or attention (Barrouillet, Gavens, Vergauwe, Gaillard, & Camos, 2009;Tam, Jarrold, Baddeley, & Sabatos-DeVito, 2010). They may also be the consequences of changes in rehearsal strategies (Gathercole, Adams, & Hitch, 1994;Hitch, Halliday, Schaafstal, & Heffernan, 1991), although it is now understood that limitations in the sensitivity of memory span in pre-school children may obscure the clear signatures of phonologically based rehearsal in older children and adults (Jarrold, 2016;Wang, Logie, & Jarrold, 2016).…”
Section: Working Memory and Its Developmentmentioning
confidence: 99%